2022
DOI: 10.1186/s12885-022-09662-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel γδ T cell-based prognostic signature to estimate risk and aid therapy in hepatocellular carcinoma

Abstract: Background Numerous studies have revealed that gamma delta (γδ) T cell infiltration plays a crucial regulatory role in hepatocellular carcinoma (HCC) development. Nonetheless, a comprehensive analysis of γδ T cell infiltration in prognosis evaluation and therapeutic prediction remains unclear. Methods Multi-omic data on HCC patients were obtained from public databases. The CIBERSORT algorithm was applied to decipher the tumor immune microenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Moreover, T cell central memory (CM) status was associated with an increased incidence of HCC, while higher numbers of γδ T cells and double-negative T (DNT) cells were linked to a reduced risk of HCC, consistent with previous ndings [31,32]. The growing recognition of the crucial role of DNT/γδT cells in tumor immune surveillance has opened avenues for adoptive reinfusion therapies, including "off-the-shelf" options currently under investigation in clinical trials for various cancers, including HCC [33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, T cell central memory (CM) status was associated with an increased incidence of HCC, while higher numbers of γδ T cells and double-negative T (DNT) cells were linked to a reduced risk of HCC, consistent with previous ndings [31,32]. The growing recognition of the crucial role of DNT/γδT cells in tumor immune surveillance has opened avenues for adoptive reinfusion therapies, including "off-the-shelf" options currently under investigation in clinical trials for various cancers, including HCC [33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 88%
“…The proposed Vδ1 + /Vδ2 + ratio emerges as a potential indicator for clinical prognosis, with higher ratios associating with more suppressed immunity and poorer outcomes. The study also identified reduced NKG2D expression in the Vδ1 + population, suggesting depressed cell activation and enhanced survival ability, while a higher pPD1 expression in the Vδ2 + population indicated suppressed cytotoxicity [58]. These results are in alignment with the research of Wang et al, who aimed to analyze γδ T cell infiltration in HCC for prognosis and therapeutic prediction [59].…”
Section: Insights Into the Utilization Of γδ T Cells In Hcc Immunothe...supporting
confidence: 84%
“…Strikingly, these immune cell infiltrations exhibited no statistical differences among different pTNM stages, affirmin g the highly immunosuppressive nature of the HCC TME across various disease stages. The authors further extended their investigation to the phenotypic profiles of circulating γδ T cells in HCC and healthy populations [58]. The analysis reveals a dominance of the Vδ2 + subset in the PB of healthy individuals, while under immune-suppressed conditions in HCC, the Vδ2 + subset is significantly depleted.…”
Section: Insights Into the Utilization Of γδ T Cells In Hcc Immunothe...mentioning
confidence: 97%
See 1 more Smart Citation
“…Lymphocytes play an important role in cancer surveillance ( 35 ). Accumulating evidence supported that the interactions of infiltrating immune cells with tumor components act as vital driving factors for tumor progression and therapeutic sensitivity ( 36 , 37 ). As the prime anti-tumor cells, CD8 + T cells can secrete IFN-γ and TNFα to destroy cancerous cells once they contact tumor cells or eliminate tumor cells by releasing perforin and granzyme B through the Fas/FasL pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%